Contemporary issues URDU-IDEOLOGICAL LIMITATIONS TO CONTEMPORARY ISLAMIC SOCIETIES - Irfan Jafar; Muhammad Saad Dhalvi (دی اسکالر, 2022)
MÒdern Muslim are facing Many Muslims since one Hundred Years.  It is because of regime Western civilization. Muslims are facing Political, Economic, Social & civilization Problems. We can get prestige by inviting non-Muslims to Islam. Knowledge is a Power that can Defeat other civilizations. We should try to combine for this purpose. Scholars of Religion & Politics should be on one stage. All propaganda of the orientalists must be rejected. They should not be allowed to disturb Muslims Countries. Muslims should live peacefully, like a family. Muslims should ignore Sectarianism in religion. It is Very Dangerous for Nations.  Allah Says in Quran: All Should Catch Rope of Allah Strongly & Should Not Be Divided. Holy Prophet Says: “Believers are like a Building, They Make Strong to one another. Most of the Muslim countries are combined geographically but they are not United physically they Believe in One Allah, One Rasool & one Kaaba, and inspite of this they are divided in different ways. They should Follow Holly Prophet (PBUH) in all their life. In this way, their all problems will be solved.